ЛЕЧЕНИЕ ЯЗВЕННОЙ БОЛЕЗНИ ЖЕЛУДКА И ДВЕНАДЦАТИПЕРСТНОЙ КИШКИ В ИСТОРИЧЕСКОМ АСПЕКТЕ - В. И. Совалкин; Л. М. Смирнова; Г. Р. Бикбавова; Э. Г. Аглиуллина; Н. С. Кокухина (Архивъ внутренней медицины, 2012)
In this review we present materials reflecting the evolution of ideas about reasons and treatment of peptic ulcer disease. Existing treatment methods don’t fully respond to our demands and expectations. First of all, it’s about a progressive growth of Helicobacter pylori’s resistance to antimicrobial drugs, which leads to the decreasing of the eradication therapy effectiveness. The analysis of historical data shows the possibility of choice of more perspective methods of peptic ulcer disease treatment.